Organizational, Leadership, and Communication Drivers of Knowledge Management in Higher Education - Iman Indrati; Henny Suharyati; Dian Wulandari (Transpublika Publisher, 2026)
Knowledge management among lecturers remains a critical challenge in higher education institutions, particularly in adapting to dynamic organizational and leadership demands. This study aims to analyze the influence of organizational support and agile leadership on lecturers' knowledge management mediated by interpersonal communication. The research addresses the limited empirical evidence on how social mechanisms and leadership adaptability shape knowledge management practices in higher education. The research population was drawn from three private universities in Bogor City. The study used a quantitative approach with an explanatory research design and involved a sample of 100 respondents. Data were analyzed using inferential statistical techniques to examine both direct and indirect relationships among variables. The results showed that agile leadership had a significant effect on knowledge management both directly and indirectly. Organizational support mediated by interpersonal communication did not show a significant direct effect on knowledge management. These findings indicate that adaptive leadership and social interaction play a more decisive role than formal institutional support. The study concludes that social mechanisms and agile leadership primarily drive lecturers' knowledge management. The findings imply that higher education institutions should prioritize leadership development and interpersonal communication strategies to enhance knowledge management practices. The novelty of the research introduces a new model of lecturer knowledge management based on the social mechanism of agile leadership.